Epileptic phenomena produced by kainic acid in laboratory rats during ontogenesis - Velísková, J; Velísek, L; Mares, P (Physiologia Bohemoslovaca, 1988)
Because of its preferential neuroexcitatory effects on the hippocampal neurones kainic acid (KA) is used for inducing partial seizures with a complex symptomatology. In this study the authors investigated the effect of intraperitoneal administration of KA, in doses of 2-16 mg/kg, on the laboratory rat during ontogenesis. The experimental animals were males aged 7, 12, 18, 25 and 90 days. The first signs of an effect in adult rats were automatisms; in young animals, jerks also appeared. The most important automatisms were wet dog shakes, which preponderated in 25-day-old and older animals, whereas in the young rats they consisted chiefly of intensive scratching. Minimal seizures with a motor pattern identical to minimal metrazol seizures were observed in all the age groups and so were generalized tonic-clonic convulsions, which appeared after large doses of KA. The systemic administration of KA is a convenient model of temporal seizures and their progressive generalization and could act as a model for testing broad spectrum antiepileptics.
Keywords: krysa rodu Rattus; Animals; pohybová aktivita; Motor Activity; věkové faktory; Kainic Acid; zvířata; kyselina kainová; mužské pohlaví; Male; modely nemocí na zvířatech; epilepsie temporálního laloku; Age Factors; inbrední kmeny potkanů; Rats; Epilepsy, Temporal Lobe; Rats, Inbred Strains; Disease Models, Animal